A Business Leader's Guide to Philosophy - Dawson, Lindsay (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book provides a unique introduction for business leaders to the philosophical lexicon of classical and contemporary ideas-for and against-that are relevant to business and those destined to lead it. Rather than presenting the reader with a 'philosophy of leadership' the author uses his experiences in academia and as a leader in business to illustrate the practical application of philosophical ideas and methodologies covering the art and science of being a business leader: motivating stakeholders to deliver the initial phase of a business plan for a new product or service; processing information (and risky 'hidden-information') that brings the company vision into reality; and ethically managing relationships to enhance the quality of decision-making and its outcomes. Creative aspiration, knowledge and ethical character are the three pillars of leadership. Within that construct, this book challenges leaders to seek their own path to self-development inspired by ideas that shape theecology of capitalism and the opportunities it provides stakeholders to endow meaning and dignity to their lives through their participation in business.
introduction -- Part 1: Some philosophical foundations -- Part 2: Managing creativity...birthing the dream -- Part 3: Interpreting information to deliver the dream -- Part 4: Ethics and business...uniting the dream makers. Conclusion -- References.
Keywords: Philosophy; Management; Strategic planning; Leadership; Business ethics; Philosophy of Management; Business Strategy and Leadership; Business Ethics